The history of Libya - Oyeniyi, Bukola Adeyemi (Greenwood histories of the modern nations., 2019)
Covers Libyan history from the prehistoric period through the Phoenician, Roman, and Islamic/Ottoman periods to Italian colonization, independence, and the 2011 uprising and civil war. Includes a timeline of significant events, providing students with an at-a-glance overview of Libya's history."--